CYTOTOXIC EFFECT OF GINGER AND BLUE PEA HERBAL FORMULATION BASED MOUTHWASH - AN IN VITRO STUDY (Cuestiones de Fisioterapia, 2025)
INTRODUCTION: Herbal mouthwash made from natural sources is used in periodontal therapy controlling bleeding, inflammation. The efficacy of herbal mouthwash is effective in reducing plaque and gingivitis when compared to chlorhexidine mouthwash. Clitoria ternatea ( blue pea) to be an effective natural remedy for a variety of ailments. Aim of the study is to evaluate the cytotoxic effect of ginger and blue pea based herbal mouth wash.